2008
DOI: 10.1007/s10265-008-0191-7
|View full text |Cite
|
Sign up to set email alerts
|

Phenology of 16 species of ferns in a subtropical forest of northeastern Taiwan

Abstract: A knowledge of fern phenology promotes understanding of the biology and ecology of ferns. In this study, the phenology of 16 fern species in a subtropical broadleaf forest (N24 degrees 46', E121 degrees 34') in northeastern Taiwan was monitored from August 1997 to August 2001. Every fern produced both fertile and sterile leaves in each year of the study. Most fertile leaves emerged in February and March, whereas most sterile leaves emerged from May to September. Most leaves reached full expansion during April-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 18 publications
3
12
0
5
Order By: Relevance
“…It is likely that the variation of approximately 3.5 h in the photoperiod over the course of a year in the coastal region of Rio Grande do Sul, together with the direct effects of changes in temperature, triggers predictable physiological responses in several species (Marchioretto et al 2007), as was observed for C. corcovadensis in the present study, as well as and for C. atrovirens and Dicksonia sellowiana in the studies conducted by Schmitt et al (2009) and Schmitt & Windisch (2012), respectively. In a study of 16 fern species in a subtropical broadleaf forest in northeastern Taiwan, Lee et al (2009) reported that leaf senescence, spore maturation and spore release all presented significant positive correlations with temperature but not with precipitation, which is in agreement with our findings for C. corcovadensis. A delay between environmental stimulus and phenological response has previously been reported (Marques & Oliveira 2004), which might also explain our finding that the C. corcovadensis phenophases were correlated with the photoperiod and temperature in the month prior to the field observations.…”
Section: Discussionsupporting
confidence: 92%
“…It is likely that the variation of approximately 3.5 h in the photoperiod over the course of a year in the coastal region of Rio Grande do Sul, together with the direct effects of changes in temperature, triggers predictable physiological responses in several species (Marchioretto et al 2007), as was observed for C. corcovadensis in the present study, as well as and for C. atrovirens and Dicksonia sellowiana in the studies conducted by Schmitt et al (2009) and Schmitt & Windisch (2012), respectively. In a study of 16 fern species in a subtropical broadleaf forest in northeastern Taiwan, Lee et al (2009) reported that leaf senescence, spore maturation and spore release all presented significant positive correlations with temperature but not with precipitation, which is in agreement with our findings for C. corcovadensis. A delay between environmental stimulus and phenological response has previously been reported (Marques & Oliveira 2004), which might also explain our finding that the C. corcovadensis phenophases were correlated with the photoperiod and temperature in the month prior to the field observations.…”
Section: Discussionsupporting
confidence: 92%
“…A sazonalidade desta fenofase foi a mais evidente dentre os outros eventos fenológicos analisados e possivelmente deve-se a característica dessa espécie em possuir folhas dimórficas (Figura 6b e c), que se manifestam na planta em um curto período de tempo e senescem logo após a liberação dos esporos (Lee et al, 2009). A ocorrência sazonal da fertilidade também foi observada em Microgramma squamulosa, samambaia epifítica com dimorfismo foliar crescendo sob clima com estação seca definida (Ranal, 1995).…”
Section: Discussionunclassified
“…Segundo Lee et al (2009), folhas férteis de espécies dimórficas possuem longevidade reduzida, visto que sua função seria somente a reprodução.…”
Section: Discussionunclassified
“…Cyathea gigantea has been included in the Appendix II of CITES and its export has been restricted (Sanjappa and Lakshminarasimhan 2011). To prevent anthropogenic interferences and export of important plant species worldwide, CITES has included many species of the genus in Appendix II (Thomas et al 2006 (Juneja et al 1990;Soltis et al 1991;Bellingham et al 1995;Arens and Balcado 1998;Simabukuro et al 1998;Bernabe et al 1999;Ough and Murphy 2004;Khare et al 2005;Schuettpelz and Pryer 2007;Chandra et al 2008;Hort et al 2008;Bhuju and Joshi 2009;Lee et al 2009;Rout et al 2009;Watkins and Cardelús 2009;Ballesteros 2010;Volkova et al 2010;Bystriakova et al 2011;Ranil et al 2011;Kiran et al 2012;Schmitt and Windisch 2012;Shukla and Khare 2012;Wang et al 2012;Neumann et al 2014) in various parts of the world. However, ecological studies on Cyathea spp.…”
Section: Introductionmentioning
confidence: 99%